2011
DOI: 10.1103/physrevb.84.214511
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in BaFe2Se3single crystals with double chains of FeSe tetrahedra

Abstract: We studied the anisotropy in physical properties of Ba 1.00(4) Fe 1.9(1) Se 3.1(1) single crystals. BaFe2Se3 is a semiconductor below 300 K. Magnetization measurements show that there is a crossover from a short-range antiferromangetic (AFM) correlations at room temperature to a longrange AFM order with TN = 255 K. The anisotropy of magnetization is consistent with the previous neutron results. This crossover is supported by the heat capacity measurement where the phasetransition peak is absent at 255 K. The s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
106
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 17 publications
15
106
0
Order By: Relevance
“…In this subsection, recent experimental efforts (Caron et al, 2011;Saparov et al, 2011;Lei et al, 2011d;Caron et al, 2012;Nambu et al, 2012) in the study of selenides with the geometry of two-leg ladders (sometimes also referred to as double chains) will be reviewed, while a description of the status of the theoretical work will be presented in the next subsection. A typical compound in this context is BaFe 2 Se 3 that contains building blocks made of [Fe 2 Se 3 ] 2− that when assembled along a particular direction leads to an array of two-leg ladder structures, as sketched in Fig.…”
Section: A Introduction and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this subsection, recent experimental efforts (Caron et al, 2011;Saparov et al, 2011;Lei et al, 2011d;Caron et al, 2012;Nambu et al, 2012) in the study of selenides with the geometry of two-leg ladders (sometimes also referred to as double chains) will be reviewed, while a description of the status of the theoretical work will be presented in the next subsection. A typical compound in this context is BaFe 2 Se 3 that contains building blocks made of [Fe 2 Se 3 ] 2− that when assembled along a particular direction leads to an array of two-leg ladder structures, as sketched in Fig.…”
Section: A Introduction and Experimentsmentioning
confidence: 99%
“…For instance, SrCu 2 O 3 is a material analogous to BaFe 2 Se 3 (Dagotto, 1999). BaFe 2 Se 3 is an insulator with a gap 0.14-0.18 eV (Lei et al, 2011d ;Nambu et al, 2012). This material has long-range AFM order at ∼250 K, low-temperature magnetic moments ∼2.8 µ B , and short-range AFM order (presumably along the leg directions) at higher temperatures (Caron et al, 2011;Saparov et al, 2011;Lei et al, 2011d).…”
Section: A Introduction and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, iron-based ladder compounds AFe 2 X 3 (A = K, Rb, Cs or Ba, and X = chalcogen) [17][18][19] have been under intensive investigation [20][21][22][23][24][25][26][27][28][29] . The AFe 2 X 3 compounds consist of FeX 4 tetrahedra, which are similar to the 2D iron-based SCs, but Fe atoms form two-leg ladder lattice giving rise to the quasi-one dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…8 BaFe 2 Se 3 is an insulator down to the lowest measured temperature with a long-range antiferromagnetic (AFM) order with T N around 255 K and short-range AFM order at higher temperatures. [9][10][11][12] It was shown that a dominant order involves 2×2 blocks of ferromagnetically aligned four iron spins, whereas these blocks order antiferromagnetically, in the same manner as the block-AFM √ 5× The Fe-S double chain in the (010) projection. w, u, v represents Fe-Fe distances of ladder rungs (w=0.2697 nm; w * =0.2698 nm) and legs (u=0.2688 nm, v=0.2720 nm; v * =0.2643 nm).…”
Section: Introductionmentioning
confidence: 99%